Development of Science and Social Studies Module Integrating Augmented Reality to Improve Elementary School Student Literacy and Numeracy Skills - Ali Ismail; Rana Gustian Nugraha; Dadan Nugraha (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesia faces ongoing challenges in literacy and numeracy skills, as highlighted by low PISA scores. This research aims to develop an innovative learning module that integrates Natural and Social Sciences (IPAS) with augmented reality (AR) technology for primary school students. Utilizing a Research and Development (R&D) methodology, this study followed the 4D model. In the Define stage, a needs analysis through literature review and field study identified gaps in current IPAS learning and limited technology integration. The Design and Development stages focused on creating an IPAS module incorporating AR, validated by experts in science, social studies, and technology, which demonstrated its validity. During the dissemination stage, the module was tested for compatibility on various Android devices and was 100% successful in both installation and uninstallation. In addition, a feasibility test was conducted using a User Experience Questionnaire (UEQ) with 24 students, showing very positive results, with scores of Attractiveness (2.63), Clarity (2.13), Efficiency (2.38), Accuracy (2.25), Stimulation (2.38), and Novelty (2.56). All scores were above the positive threshold (>0.8). These findings show that the integration of AR in the IPAS module not only increases student engagement but also supports literacy, numeracy, and independent learning